Old and New Flavors of Flame (Furnace) Atomic Absorption Spectrometry. (12th October 2011) - Dionísio, Amália Geiza Gama; de Jesus, Amanda Maria Dantas; Amais, Renata Stábile; Donati, George Luís; Miranda, Kelber dos Anjos; Guerra, Marcelo Braga Bueno; Nóbrega, Joaquim Araújo; Pereira-Filho, Edenir Rodrigues
Abstract : This paper presents some recent applications of Flame Atomic Absorption Spectrometry (FAAS) to different matrices and samples. The time window selected was from 2006 up to March, 2011, and several aspects related to food, biological fluids, environmental, and technological samples analyses were reported and discussed. In addition, the chemometrics application for FAAS methods development was also taken into account, as well as the use of metal tube atomizers in air/acetylene flame. Preconcentration methods coupled to FAAS were discussed, and several approaches related to speciation, flotation, ionic liquids, among others were discussed. This paper can be interesting for researchers and FAAS users in order to see the state of the art of this technique.